Cumulative triglyceride-glucose index and hypertension risk : a longitudinal cohort study - Wu, Zhaogui; Wu, Dan; Xu, Sichi; Borné, Yan; Lan, Yulong; Chen, Shuohua (BMC Public Health, 2025)
BACKGROUND: Prior research has established a positive association between the single-measured triglyceride-glucose (TyG) index and hypertension. Nevertheless, longitudinal studies addressing the enduring impact of TyG index on incident hypertension are lacking. This study sought to explore the association between cumulative TyG index (cum-TyG) and incident hypertension, especially obesity-related hypertension (ORHT). METHODS: A total of 21,017 individuals [mean (SD) age: 48.5 ± 11.7 years, male (%): 14,544 (69.2)] without hypertension were recruited from the Kailuan Study. The cum-TyG was determined by multiplying the mean TyG index by the time intervals between successive visits. Multivariable Cox regression models were used to investigate the association of cum-TyG with incident hypertension, ORHT, and non-obesity-related hypertension (NORHT). RESULTS: Over a median follow-up of 9.59 years, 7556 individuals developed hypertension. Among them, 1505 cases were ORHT and 6051 cases were NORHT. After controlling for potential confounders, compared to the TyG Quartile 1, the adjusted hazard ratios (HR) and 95% confidential intervals (95% CIs) for hypertension were 1.06 (0.99 to 1.13), 1.09 (1.02 to 1.17) and 1.21 (1.13 to 1.30), respectively, for TyG Quartiles 2, 3, and 4 (P for trend < 0.001). Each 1-SD rise in cum-TyG was associated with a risk of 1.08 (95% CI: 1.05 to 1.11) for overall hypertension, 1.22 (95% CI: 1.16 to 1.28) for ORHT and 1.07 (95% CI: 1.04 to 1.10) for NORHT. In addition, longer exposure to elevated TyG was significantly associated with increased hypertension risk (P for trend < 0.001). Compared to the 0-year exposure period, the risks associated with the 6-year exposure period were 1.36 (95% CI: 1.26 to 1.47), 2.86 (95% CI: 2.47 to 3.32), and 1.22 (95% CI: 1.12 to 1.33), for overall hypertension, ORHT and NORHT, respectively. CONCLUSIONS: Elevated TyG index accumulation is positively associated with an increased risk of developing hypertension, especially obesity-related hypertension.
© 2025. The Author(s).
Keywords: Humans; Male; Hypertension/epidemiology; Longitudinal Studies; Female; Middle Aged; Triglycerides/blood; Adult; Blood Glucose/analysis; Risk Factors; China/epidemiology; Obesity/complications; Incidence